Menelusuri Kearifan Kehidupan dalam Cerita Rakyat Rejang Lebong: Analisis Nilai-nilai yang Diungkap - Ifnaldi Ifnaldi; Tiara Wulandari; Agita Misriani (Institut Agama Islam Negeri Curup, 2023)
The lack of knowledge of the community and the younger generation about folklore in their own area makes the life values contained in them just get buried. This study aims to describe the values of life in the folklore of Rejang Lebong. This research is a qualitative descriptive research with a content analysis approach. Value data collection techniques, namely documentation studies and literature studies with data sources in the form of documents from the Rejang Lebong folklore in the form of quotations showing life values which are analyzed by reading, identifying, classifying, describing, and presenting research results based on life-values theory according to Haris Supratno. The results showed that twenty Rejang Lebong folktales reflected life values which included educational values (motivation (spirit), interest (aspirations), high curiosity), religious values (grateful, praying, worshiping), moral values (attitude qanaah, persistent, patient, never give up, tolerance, warm-hearted, honest, responsible, polite, confident, trustworthy), leadership values (good leader attitude, wise, realistic, creative, innovative), heroic values (warrior nationalism spirit valiant), the value of courage (trying new things, defending the truth), the value of simplicity (simple in living life without exaggeration), the value of mutual cooperation (help, cooperation), the value of sacrifice (voluntary in fighting for the truth, family, lover).